Clearance of different strains of Mycoplasma pulmonis from the respiratory tract of C3H/HeN mice. - Davidson, M K (1988)
Pathogen-free C3H/HeN mice were exposed by aerosol to Mycoplasma pulmonis PG34(ASH), UAB 5782C, M1, UAB T, or UAB CT, and clearance of mycoplasmas from the nasal passages, trachea, and lungs was determined during the first 72 h postinoculation (PI). There were differences among strains of mycoplasmas in physical removal of organisms and in killing by nonspecific factors in the nasal passages and trachea. The avirulent strain, PG34(ASH), was quickly removed from the nasal passages and trachea. Physical removal of the other mycoplasmal strains occurred slowly, with 60 to 89% of the radioactive label remaining in the nasal passages and trachea even after 72 h. There were significant differences in killing among mycoplasmal strains by nonspecific host mechanisms in the nasal passages, trachea, and lungs. Strain UAB T was quickly killed at all levels of the respiratory tract. Strains UAB 5782C and M1 were killed at all three sites by 2 to 4 h PI. The most virulent strain, UAB CT, was killed much more slowly than the other strains. However, there was no statistical difference in the relative numbers of mycoplasmas present in the lungs at 72 h PI among strains UAB CT, UAB 5782C, and M1. These studies showed that the different mycoplasmal strains were cleared from the respiratory tract by different mechanisms and suggest that the differences in virulence among the mycoplasma strains can be explained, in part, by the differences in elimination of the organisms from the respiratory tract by nonspecific host defense mechanisms.